Re-Framing Identities : Architecture's Turn to History, 1970-1990 - Moravánszky, Ákos; Lange, Torsten (East West Central: re-building Europe, 1950-1990 ;, 2017)
The international authors of this three-volume work show Europe's post-war architecture in a new light. In spite of geo-political divisions and national differences, the developments in East and West are seen in context for the first time - a mutual perception, the transfer of knowledge, and cooperation, opened avenues across boundaries. Each volume is dedicated to a leading subject and its unfolding across overlapping periods of time.